Ripening for improving the quality of inoculated cheese Rhizopus oryzae - SOLIKAH ANA ESTIKOMAH; SUTARNO SUTARNO; ARTINI PANGASTUTI (Nusantara Bioscience, 2010)
Abstract. Estikomah SA, Sutarno, Pangastuti A 2010. Ripening for improving the quality of inoculated cheese Rhizopus oryzae. Nusantara Bioscience 2: 1-6. Cheese is dairy product resulted from fermented milk in which the fermentation process can be done by lactic acid bacteria or fungus. Rhizopus oryzae is able to produce lactic acid, protease, and lipase. The ripening process changes the taste and texture. The purpose of this study is ripening to improve the quality of inoculated cheese R. oryzae. In this research, the ripening was conducted the concentration variation of temperature (5oC, 10oC, 15oC), and time (7 days, 14 days). The procedure of research consisted of two steps, namely un-ripened cheese preparation followed by ripening cheese preparation. Cheese produced in this study analyzed the value of pH, fat content, protein content, amino acid levels and identification of microbe with ANOVA then followed by DMRT at 5% level of significance. Data results were analyzed with the like’s nonparametric statistical test, followed by Fridman Wilcoxon Signed Rank Test (WSRT) at 5% level significance. The results showed that the preferred ripened cheese panelist was at a temperature of 15oC for 14 days. Ripening conditions affect pH, fat content, protein content and do not affect the levels of amino acids that formed ripened cheese. The best quality ripened cheese, i.e. at a temperature of 15°C for 14 days, had a pH value of 4.40, the highest protein content of 9.78%, and fat content of 35.02%. The results of identified microbe in un-ripened cheese and ripened cheese include Enterococcus hirae (Enterococcus faecalis), Bacillus subtilis, and Aspergillus sp.